Topical Protease Inhibitor Decreases Anal Carcinogenesis in a Transgenic Mouse Model of HPV Anal Disease - Laura C. Gunder; Hillary R. Johnson; Evan Yao; Tyra H. Moyer; Heather A. Green; Nathan Sherer; Wei Zhang; Evie H. Carchman (Viruses, 2023)
Anal cancer is a major health problem. This study seeks to determine if the topical protease inhibitor Saquinavir (SQV), is effective at the prevention of anal cancer in transgenic mice with established anal dysplasia. K14E6/E7 mice were entered into the study when the majority spontaneously developed high-grade anal dysplasia. To ensure carcinoma development, a subset of the mice was treated with a topical carcinogen: 7,12-Dimethylbenz[a]anthracene (DMBA). Treatment groups included: no treatment, DMBA only, and topical SQV with/without DMBA. After 20 weeks of treatment, anal tissue was harvested and evaluated histologically. SQV was quantified in the blood and anal tissue, and tissue samples underwent analysis for E6, E7, p53, and pRb. There was minimal systemic absorption of SQV in the sera despite high tissue concentrations. There were no differences in tumor-free survival between SQV-treated and respective control groups but there was a lower grade of histological disease in the mice treated with SQV compared to those untreated. Changes in E6 and E7 levels with SQV treatment suggest that SQV may function independently of E6 and E7. Topical SQV decreased histological disease progression in HPV transgenic mice with or without DMBA treatment without local side effects or significant systemic absorption.